Dairy cows' responses to 2 separation methods after 3 months of cow-calf contact - Vogt, Anina; Waiblinger, Susanne; Palme, Rupert; König von Borstel, Uta; Barth, Kerstin; Justus Liebig University Giessen (My University, 2025)
Weaning and separation remain among some of the biggest challenges for cow-calf contact systems, making the development of practical and low-stress separation methods mandatory for future success of these systems. This study aimed to compare behavioral and physiological responses of dairy cows to separation from their calves after 3 mo of full-time contact, with either the 2-step method (NF, 2 wks full-time contact while calves wore a nose flap, 1 wk fence-line contact before total separation, n = 18) or by gradual reduction of contact time between cow and calf (GR, 1 wk half day contact, 1 wk morning contact, 1 wk fence-line contact before total separation, n = 18). Vocalizations and searching behavior were observed on 4 d/wk from 1 wk before separation until 1 wk after total separation. During the same period, lying behavior and rumination time was automatically assessed via accelerometers and pressure sensors. Fecal and blood samples were collected twice per week from day −1 until +23 relative to separation start for analysis of fecal cortisol metabolites and the immune response. Milk yield in the parlor was continuously recorded. Statistical analysis was conducted using linear mixed effects models. We found no difference between the 2 separation methods in any of the examined behavioral and physiological response variables. However, a significant increase in vocalizations and searching behavior compared with baseline was present with both methods. Furthermore, there was a transient increase in physiological distress markers and a short-lived retention of milk yield at initiation of treatments, indicating that both methods induced distress for the cows. Descriptively, there were large interindividual differences between cows as well as a different temporal distribution in occurrence of behavioral responses, as GR cows vocalized most frequently during the week with fence-line contact and after total separation from the calf, while NF cows reacted strongest during the 2 wk while calves wore the nose flap. Milk yield was higher in NF than GR cows during the 2 wk while GR calves had time-restricted access to their dams and NF calves were prevented from suckling, but showed no difference afterward. However, similar evening milk yields of GR cows in the weeks with half-day and morning contact, indicated that the weekly reductions in contact time worked in a rather stepwise than gradual manner, which warrants further improvement of the GR method. Taken together, results showed that cows experienced distress during separation with the GR method, when implemented over 3 wk in 3 steps, as well as with the NF method, but differences between individuals were considerable.
Keywords: ddc:630